An IoT compliant control system for automation of liquid nitrogen filling of clover Ge detectors at IUAC, New Delhi. Issue 1 (2022) - Dutt, Rajendra Nath; Santhi, R. Ruby; Yashraj,; Gurjar, R.K.; Saini, S.K.; Rana, H.; Singh, R.P.; Muralithar, S.
Abstract: This paper reports development of a liquid nitrogen filling control system for high purity germanium detectors of national gamma facility at Inter University Accelerator Centre, New Delhi. The control system has been developed to provide unattended facility of keeping the detector cryogen levels topped up without intervention. The system has been designed using latest technology hardware and software components to provide good performance as well as connectivity, automation and reliability features. The system has been used on a regular basis and has proven to be a reliable facility.